Budidaya Maggot Sebagai Alternatif Pakan Sumber Protein Untuk Ternak Itik - Mohammad Hasil Tamzil; Budi Indarsih; I Nyoman Sukartha Jaya; Ni Ketut Dewi Haryani (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The counseling activity was carried out to provide skills on the maggot farming system to members of the Monggelemong duck farmer group, in Dasan Cermen, Sandubaya, Mataram city in an effort to provide alternative protein source for feed ingredients in duck feeding. The activity was held in collaboration between the Monggelemong duck farmer group and teaching staff of the Poultry Production Laboratory, Faculty of Animal Science, University of Mataram. Counseling was carried out using lecture methods, discussions and continued with demonstration plot activities or direct practice which was attended by all participants. Practical activities start with the process of hatching BSF (Black Soldier Fly) eggs, growing maggot, harvesting maggot and making germs or larvae. All series of activities went smoothly and all farmers involved seriously. Through this activity the duck farmers were able to gain skills on maggot farming which can be used as duck feeding. Thus it can be concluded that this community service activity can provide additional skills to members of the Monggelemong duck famer group, in Dasan Cermen Sandubaya, Mataram city regarding the maggot farming system as an alternative source of protein feed for duck feeding.